Asrâr al-Mutasyâbih al-Lafdzî Fi al-Qur’an ‘Inda Ibnu al-Zubair al-Gharnathi - Rochmad Abdurrasyid; Muhammad Perdana Putra (Universitas Darussalam Gontor, 2017)
Among the specificity of sentence in the verses of Qur'an is seen on some repetition of similar words in several places. According to orientalist, that it is a futility. Whereas Muslim scholars see that this is the side of the miracles of the Qur'an, so there are some works related to Mutasyâbih al-Lafdzi, including the works of Imam Zarkasyi, Suyuthi, Sakkhawi, Abdullah al-Razi, Qadhi Badrun Din, and according to the best Muslim scholar is the work of Ibn Zubair Gharnathi. This study focuses on Surah an-Nisa to see the secrets of Mutasyâbih al-Lafdzi according to Gharnathi. It is found that the addition occurs to corroborate and explain the previous phrase in a verse. Putting the words or phrases that should be behind in an arrangement to show the beauty of the composition of the verse at the same time indicates the main purpose of a verse. While hiding or even removing a particular word or phrase to facilitate in reading the Qur'an.